POLA KEMITRAAN PETANI DALAM PEMASARAN RUMPUT LAUT DI DESA KOLESE KECAMATAN PASIKOLAGA KABUPATEN MUNA - Sarvini, Hikmanila; Abdullah, Sukmawati; Arimbawa, Putu (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
This study aims to: (1) analyze the pattern of farmer partnerships in seaweed marketing in Kolese Village, Pasikolaga District, Muna Regency, (2) Analyze how partnerships in the seaweed marketing sector in Kolese Village, Pasikolaga District, Muna Regency, affect farmers' income. This study was carried out in November 2022 in the Kolese Village, Pasikolaga District, Muna Regency, with a total of 20 respondents chosen by a straightforward random selection method. data analysis using class intervals and descriptive statistics. The results of this study show that (1) In Kolese Village, Pasikolaga District, and Muna Regency, farmer partnerships in the overall trade pattern are fairly excellent, and client patron partnership patterns in seaweed marketing channels are good. The price in both partnership models used by seaweed farmers in the Kolese Village, Pasikolaga District, and Muna Regency is quite good, (2) Seaweed plan income is relatively low below the average monthly net income of informal workers in Muna Regency agricultural farming. However, from a nominal, the income of farmers who carry out the client-patron partnership pattern is higher than farmers who carry out the general trade partnership pattern.